2000
DOI: 10.1093/jexbot/51.342.41
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotope natural abundances (δ15N and δ13C) to integrate the stress responses of wild barley (Hordeum spontaneum C. Koch.) genotypes

Abstract: To integrate the complex physiological responses of plants to stress, natural abundances (delta) of the stable isotope pairs 15N/14N and 13C/12C were measured in 30 genotypes of wild barley (Hordeum spontaneum C. Koch.). These accessions, originating from ecologically diverse sites, were grown in a controlled environment and subjected to mild, short-term drought or N-starvation. Increases in total dry weight were paralleled by less negative delta 13C in shoots and, in unstressed and droughted plants, by less n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 30 publications
6
96
1
Order By: Relevance
“…While d 15 N signatures have successfully been used to interpret source nutrients (Dawson et al 2002;Robinson et al 2000), we found our data difficult to interpret because of the high variability and lack of consistent patterns within or among epiphyte taxa (Fig. 4b).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While d 15 N signatures have successfully been used to interpret source nutrients (Dawson et al 2002;Robinson et al 2000), we found our data difficult to interpret because of the high variability and lack of consistent patterns within or among epiphyte taxa (Fig. 4b).…”
Section: Discussionmentioning
confidence: 92%
“…4b). This high variability is likely a combination of source nutrient signature, a possible series of integrated fractionation events (Dawson et al 2002;Robinson et al 2000), and variability among species within each taxon. The most notable result for d 15 N values was the depletion trend with increasing elevation in host trees.…”
Section: Discussionmentioning
confidence: 99%
“…Salt tolerance in cultivated wheat can be improved by using the allelic repertoire offered by wheat wild relatives. For this reason, the existing variability currently available in gene pools must first be characterized at physiological, morphological and genetic levels (Robinson et al 2000;Nevo 2001).…”
Section: Discussionmentioning
confidence: 99%
“…An array of salinity-drought combinations modifies d 15 N in shoots and roots relative to controls, with tolerant genotypes exhibiting higher shoot d 15 N than susceptible genotypes (Table S1), suggesting that stress conditions influence N uptake and ⁄ or assimilation (Handley et al, 1997;Ellis et al, 2002;Yousfi et al, 2009Yousfi et al, , 2010 reported in cereals as a response to salinity (Yousfi et al, 2009(Yousfi et al, , 2010 and deficit irrigation (Robinson et al, 2000;Raimanová & Haberle, 2010). Reduced g s as a result of either salinity or water stress, or a combination of both, would lead to a reduction in the loss of ammonia and nitrous oxide, hence decreasing d 15 N (Farquhar et al, 1980;Smart & Bloom, 2001).…”
Section: N Of Shoots and Rootsmentioning
confidence: 97%